Design and performance investigation for substrate filler in protected horticulture - WEI Yuyong; LU Jun; SHENG Kuichuan; QIAN Xiangqun; SHEN Junfeng (浙江大学学报. 农业与生命科学版)
Substrate filler is one of the important equipments for mechanization growing seedlings. Mechanized breeding has been developed as a new horticulture technology in recent ten years worldwide. It has become a professional commercial seedling production way in many countries, particularly in Europe and America. Development of substrate filler machine and seedling production line can promote the seedling production in protected horticulture. With the rapid development of modern horticultural production, the demand for substrate filler is increasing dramatically. However, the composition of substrate filler is very complicated in structure. It is difficult to develop a single type of substrate filler to meet the demand of all crop growth. Furthermore, automatic feeding device is complex and expensive in the fierce competition in the growing market. Therefore, people are looking for more convenient and effective seedling medium automatic feeding devices, which can not only fill substrate in plugs, but also mix matrix uniformity according to various specifications.Now, the design, performance testing and filled result of TLZ-400 type substrate filler were reported. This filler was composed of material tank, lifting device, matrix tray conveying agency, vibration, rotating scraper, bodies brush, and electrical control components. The working principle is that the mixing substrate is transported to plug over and fall into the tray on a conveyor belt after promotion agencies raise, followed by scraper shaving, vibration shaking, and brush cleaning, so as to achieve the purpose of smooth and uniform mixing of substrate in plugs. The purpose was to investigate and confirm the main technical parameters of TLZ-400 type substrate filler. The technical characteristic parameters, productivity, and power consumption of TLZ-400 type substrate filler were measured by using selected perlite (50%), organic fertilizer and black earth (30%), and sawdust (20%) as mixed substrate. Substrate uniformity, sample standard deviation, and sample coefficient variation were also analyzed by using substrate sampling methods of 18 - 36 holes in plugs.Results showed that supporting power of this substrate filler was 1 180 W and the production capacity ranged from 50 to 380 tray/h. When the vibration status was off or on, the total standard deviation was 1.485 or 1.247, and the total coefficient variation was 7.94% or 6.70%, respectively.We conclude that the TLZ-400 type substrate filler is suitable for matrix filler, vibration, cleaning, and recycling. It is ready for seeder sowing after the substrate is uniformly filled in nursery plug.